Internalisasi Nilai-Nilai Pendidikan Agama di Sekolah: Perspektif Manajemen Pendidikan Islam - Abdul Wahid Zaini; Rusdi, Naemuddin; Suhermanto, Suhermanto; Ali , Wafa (Journal of Educational Management Research, 2022)
This paper aims to analyze the process of internalizing the values of religious education at Baddridduja Probolinggo Middle School Full Day School. This study uses a qualitative approach to the type of case study. The informants consisted of school principals, teachers, parents, and students. The research results show that; 1) The process of internalizing religious values at Badridduja Fullday School is carried out through; a) People, namely building commitment, deepening the teacher's understanding of learning tools, broadening the teacher's religious insights, and integrating religious values in subjects, b) Environment, namely familiarizing students with good deeds such as dhuha prayers in congregation, fardlu prayers, tadarus and habituation of noble morals such as charity, 4S culture (Smiles, Greetings, Greetings, Courtesy), and Tomato Culture (Please, Sorry and Thank You), c) Behavior, namely students can apply good deeds and noble character habits outside of school. 2) The implication is; a) The formation of a religious character, b) The lack of radical thoughts and attitudes from students.